KEMAMPUAN PEMECAHAN MASALAH MATEMATIK PADA MATERI BANGUN DATAR SISWA SMP KELAS VII - Lina Rosmawati; Euis Eti Rohaeti; M Afrilianto (IKIP Siliwangi, 2018)
This study aims to increase the problem-solving ability of students of Class VII SMP on the building of flat and rectangular. This type of research is a classroom action research. By using a descriptive qualitative method. This research was conducted on the students of Class VII of Junior High School in Karawang with 38 students. The instruments used are students' Mathematical Problem Solving abilities, cycle I and II tests after giving the action. The result of the test pad of cycle 1 is only 37.1% of students who can answer the problem well. And in cycle 2 the result of the test increases from cycle 1. Based on the indicator, it is concluded that the mathematical problem-solving ability of the seventh-grade students of SMP on the building of flat and rectangle is low.